Pengaruh Body Image Terhadap Kepercayaan Diri Remaja Putri - tian hayyin Mubarokah (ROSYADA: Islamic Guidance and Counseling, 2023)
Body image is a multidimensional, subjective, and dynamic concept that includes one's perception. Thoughts, and feelings about his body. Body image is not limited to a person's aesthetic characteristics, but also considers his health condition, skills, and sexuality. A person will be confident when the person realizes his ideal body shape and the person is satisfied to see his body shape, then the body image that is formed is also positive. Conversely, if someone views his body as not ideal, such as his face is less attractive, which is formed into a negative and it can be said that the person is not confident. The purpose of this study was to describe the effect of body image on the self-confidence of teenage girls in grade xi at SMAN 1 Geger Madiun. This study uses a quantitative approach to the type of correlational research. The data collection technique in this study used a questionnaire technique. Meanwhile, to analyze the data in this study using a simple linear regression formula. Based on the data analysis, it was found that there was a significant influence between body image on the self-confidence of the eleventh grade girls at SMAN 1 Geger Madiun. This is known from the results of calculations using SPSS, namely Fcount (19.965) > Ftable (1.97) so that Ho is rejected. While the magnitude of the effect is 35.7%. The effect of body image on the self-confidence of adolescent girls in class XI at SMAN 1 Geger Madiun is in the medium (good) category. This is obtained from the results of student questionnaires with details of 64.3% with a frequency of 64 out of 184 respondents. The medium category in this study was considered good because the effect of body image on the self-confidence of the eleventh grade girls at SMAN 1 Geger Madiun was balanced.keywords : Body Image, Confidence